Social Innovation and Crowdsourcing in Healthcare - Tucker, Joseph D (International Journal of Human and Health Sciences (IJHHS), 2024)
In 1907, the crowd at a county fair accurately estimated the weight of an ox. The median estimate of the crowd was more accurate than estimates from farmers and other experts. This startling observation demonstrates the wisdom of the crowds or communities in specific contexts. Crowdsourcing is the process of having a group of people collectively solve a problem, then share back solutions with the community. Crowdsourcing approaches have been used to identify social innovations, iteratively develop interventions, spur community engagement, and inform guideline processes. This talk will provide practical tools related to crowdsourcing for health, share open access resources, and introduce a recently developed WHO/TDR guide on participatory health approaches. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S8